The Professional Competences of Native English Speaking Teacher as Viewed by Students - Ruqoyah Yulia Hasanah Dhomiri; Ekaning Dewanti Laksmi; Nur Mukminatien (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: Millennium development requires schools to prepare their students to have proper English skills. It makes some schools hire native speaker as the expert of English. However, it is known that not all native speaker can teach English. They may be an expert in using English, yet not the expert of teaching English because the lack of professional competences. In this case, it is needed to investigate the native teacher professional competences based on the students' view, since the students were the people who experienced to be taught by the native teacher. In this study, it was found that the native teacher seemed to be more suitable for teaching the higher achiever students since they could follow the native teacher's explanations and instructions. Meanwhile, for the lower achiever students, being taught by the native teacher was challenging. This study aimed to investigate the professional competences of a native teacher as viewed by the students. Abstrak: Perkembangan Milenium mengharuskan sekolah mempersiapkan siswa mereka untuk memiliki keterampilan bahasa Inggris yang memadai. Hal itu membuat beberapa sekolah mempekerjakan penutur asli sebagai guru bahasa Inggris. Namun, diketahui bahwa tidak semua penutur asli dapat mengajar bahasa Inggris. Mereka mungkin ahli dalam menggunakan bahasa Inggris, namun belum tentu ahli mengajar bahasa Inggris karena kurangnya kompetensi profesional. Dalam hal ini, di perlukan penyelidikan terhadap kompetensi profesional guru penutur asli bahasa Inggris berdasarkan pandangan siswa, karena siswa adalah orang-orang yang berpengalaman dalam diajar oleh penutur asli. Dalam penelitian ini, ditemukan bahwa guru penutur asli bahasa Inggris tampaknya lebih cocok untuk mengajar siswa berprestasi karena mereka dapat mengikuti penjelasan dan instruksi guru tersebut. Sementara itu, bagi siswa berprestasi rendah, diajar oleh guru penutur asli bahasa Inggris adalah sebuah tantangan.